The Relationship Between The Anxiety Level of The Elderly with Attitudes Towards Death in Penanggung Village Maesan district, Bondowoso Regency - Rany Agustin Wulandary (D'Nursing and Health Journal (DNHJ), 2023)
Background: Most people feel worried when they are about to enter old age. This is due to the negative stigma against the elderly where most consider the elderly to be someone who is no longer productive, has no zest for life, has many illnesses, often forgets, and tends to experience social decline. Coupled with the occurrence of physical changes where all begin to experience a decline which will eventually face death. The elderly's perception of death, especially when facing physical and mental illness that arises, causes anxiety for the elderly. Methodology: The research design used is correlational with a cross sectional approach. The instrument used to measure anxiety is by using the hars scale and for measuring attitudes by using a questionnaire in the form of a Likert scale. The sampling technique in this study was a total sampling of 40 elderly people in the village of Penanggungan Maesan District, Bondowoso Regency. Results: The results of the research based on the Chi Square correlation test were obtainedþ values= 0.000 which means less thanα= 0.05 then that H0 is rejected and H1 is accepted which means that there is a significant relationship between the level of anxiety of the elderly and attitudes towards death. Conclusion: There is a relationship between the level of anxiety and the attitude of the elderly in dealing with death, so it is necessary to hold several interventions to change the perception of the elderly in dealing with death so that they no longer experience anxiety.